Racial discrimination, John Henryism coping, and behavioral health conditions among predominantly poor, urban African Americans: Implications for community‐level opioid problems and mental health services. Issue 5 (21st February 2019) - Jones, Shawn C. T.; Brooks, Jennifer H.; Milam, Adam J.; Barajas, Clara B.; LaVeist, Thomas A.; Kane, Erika; Furr‐Holden, C. Debra M.
Abstract: The current study examined the relationship between John Henryism Active Coping (JHAC), experiences of racial discrimination, and behavioral health outcomes in a community sample of 319 Black adults. Assessments included primary health care screenings as well as self‐reported survey questions to assess JHAC, experiences of discrimination, and self‐reported behavioral health. Logistic regression models, adjusted for control variables, found a significant relationship between JHAC and having an opioid problem (odds ratio [ OR ] = 0.95, p = 0.003) and needing mental health services ( OR = 0.95, p < 0.001), such that higher levels of coping were associated with lower odds of reporting an opioid problem and needing mental health services. Notably, racial discrimination was not significantly independently associated with behavioral health. Implications for interventions and community programming are discussed.